Collective Expertise behind the Urban Planning of Munkkiniemi and Haaga, Helsinki (c. 1915) - Karppinen Emilia (Routledge, 2025)
This chapter focuses on demonstrating the existence of specific experts—architects, engineers, and businessmen—and their participation in the planning process of Munkkiniemi and Haaga. It addresses the need to acknowledge the diverse expertise behind urban planning during its formative period, before World War I. The chapter aims not to neglect the importance of Eliel Saarinen as a planner, but to discover who the other actors behind the planning of Munkkiniemi and Haaga were, and an overall understanding of how each of their work contributions was connected. It concerns what kind of expertise was needed to gain this information and by whom it was collected. The chapter shows how the necessary knowledge for making the plans was gained collectively and how the concrete planning was the collective action of various individuals. With The Munkkiniemi and Haaga plan, the planning of Greater Helsinki aroused interest among contemporary European and North American urban planning and also awakened a broad interest globally.
Urban Histories of Science. Making Knowledge in the City, 1820-1940